Development of four grass species irrigated with effluent of domestic - Piedade, Aline Regina; Cruz, Raimundo Leite [UNESP]; Campos, Sérgio [UNESP]; Boas, Roberto Lyra Villas [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2009)
This research aimed to compare the development of four grasses species irrigated by dripping with an effluent from a domestic wastewater station treatment in a small rural community, and supply water from Sabesp. For this purpose, an experiment was conducted in a greenhouse at the FCA/UNESP (Botucatu - SP) for 12 months in a completely randomized 4 × 3 factorial design, with four replications, totalizing 48 parcels. Grass species used in this experiment were: Santo Agostinho (Stenotaphrum secandatum (Walt.) Kuntze); Bermudas (Cynodum dactylon); Esmeralda (Zoysia japônica) and São Carlos (Axnopus sp). The treatments were: T1- Irrigation with re-use; T2- Irrigation with re-use + chemical fertilization and T3- Irrigation with supply water from Sabesp + chemical fertilization (control). Data were submitted to comparison of means by Tukey's test at 5 %. The results showed that nitrogen in the wastewater was enough for the good development of the grass species. However, its use caused higher potassium loss.
Desenvolvimento vegetativo de quatro espécies de grama irrigadas com efluente doméstico
Keywords: Effluent; Grass; Irrigation; Re-use water; Sludge